Pengenalan Aspek Pemasaran Dalam Bisnis Kepada Generasi Muda Pelaku UMKM di Purwokerto - Grace Maria Fitricia; Slamet Slamet (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The ability for young entrepreneurs nowadays in the middle of dynamic economic globalization environment is a worthy skill and have to be enhanced. Beside giving a chance for individuals to improve economically, entrepreneurship ability is important to be enhanced and improved to motivate creativity, innovation and open the job vacancy. One of the important knowledge and skill to become a young entrepreneur is capable in marketing aspect . The purpose of this community service activity is to help young entrepreneurs whether they are new or is in business now. In this community service activity, the method that are used is knowledge transfer through socialization dan discussion about marketing aspects in business with sharing session and question answer activity about marketing strategy and the problem that occur. The result is giving the more knowledge for the young entrepreneurs in selling their product or services